Riley’s Emotional Growth Across Inside Out and Its Sequel: A Psychological Approach - Syahbana, Aqilla Mely; Amalia, Syahara Dina (Universitas Muhammadiyah Barru, 2026)
This study aims to analyze Riley's emotional growth from childhood to youth and how it impacts her relationships with other characters. The research employs a qualitative approach, with the films Inside Out (2015) and Inside Out 2 (2024) serving as the subjects, and emotional growth as the object of study. Data were collected from primary sources include scenes and dialogues from the films and secondary sources from journals, books, and articles, through techniques such as multiple film viewings, online browsing, note-taking, and categorizing data based on emotional growth phases. This data was then analyzed using thematic analysis, which involved data reduction, data presentation, and conclusion drawing. The findings indicate that Riley's emotional development, particularly in recognizing, understanding, and managing her emotions, significantly improved the quality of her social relationships with family and friends. Despite initial challenges in emotional regulation that caused tension, her developing ability to honestly accept and express emotions, alongside growing empathy and improved communication, ultimately resulted in enhanced social competence, resilience, and stronger relationships.